الأغنية الشعبية النسوية في منطقة وادي سوف –الدلالة والوظيفة - عبابة، الطاهر, عبيد، وحيد (جامعة الوادي Universty of Eloued, 2019)
إن الأدب الشعبي هو عبارة عن تتويج لخبرات الإنسان ومعارفه وأحاسيسه تمثله عدة فنون شفوية منها الحكاية ,المثل ,اللغز, النادرة , النكتة والقصيدة والأغنية الشعبية ,وله دور كبير في تجسيد هوية الشعوب بالمحافظة على أعرافها وتقاليدها وعاداتها ومعتقداتها ومختلف طقوسها واحتفالاتها بمناسباتها المختلفة . وإيمانا منا بأهمية المحافظة على الموروثات الثقافية بإعتبارها المرآة العاكسة لصور نابضة عن حياة الشعوب وعاداتها ومُثلها وطرائق ممارستها للحياة , وقع اختيارنا على هذا الموضوع , لأن الأغنية الشعبية هي أكثر الأشكال التعبيرية الناطقة بلسان المرأة التي عبرت فيها –على مرِّ الزمن –على طموحاتها وآمالها وآلامها وعن مختلف انشغالاتها اليومية ,فقدغنَّت المرأة لنفسها ورضيعها, لطفلها وزوجها , محبة وكارهة ,راضية وغاضبة ,منكسرة وحالمة بالمستقبل ,عبرت فيها عن خضوعها لتسلط الرجل مع رضاها بذلك ,محاولة التمرد حيناً ,وإثبات ذاتها احيانا أخرى . وقد استخرجنا منها بعض الدلالات معتمدين في ذلك على المنهج النفسي والمنهج الانثروبولوجي والمنهج التاريخي ,وأهم الوظائف التي تؤديها في حياة المرأة والمجتمع ,معتمدين تصنيف العالم ألان مريام وهي وظائف سيكولوجية وبيولوجية وسوسيولوجية. Folk literature is a culmination of human experiences, knowledge and feelings represented by several oral arts such as the story, the proverbs, the puzzle, the rare, the joke, the poem and the folk song. It has a great role in embodying the identity of the people by preserving their customs, traditions, customs and beliefs. Believing in the importance of preserving cultural heritage as the reflective mirror of images of peoples' lives, habits and practices, we chose this subject because the popular song is the most expressive form of women's speech in which, over time, it expresses its ambitions, hopes and pains. The woman lost to herself and her baby, to her child and her husband, loving and hateful, satisfied and angry, broken and dreamy in the future, in which she expressed her submission to dominate the man with her consent to this, We have derived some of these indications, relying on the psychological approach, the anthropological approach, the historical method, and the most important functions that they perform in the life of women and society. They are based on the classification of the world, ie, psychological, biological and sociological.
Keywords: الأغنية الشعبية - الدلالة - الوظيفة; Popular song - significance - the job